Advancing sustainable performance management in the hospitality industry: A novel framework based on a health-inclusive balanced scorecard - Tahniyath Fatima (16500229) (2023)
Sustainable tourism garnered interest as the United Nations set goals that could be met by the tourism industry. However, sustainability performance metrics have been peripheral in the hospitality industry. This study pushes for the importance of performance management in the hospitality industry through proposing a multi-dimensional sustainability balanced scorecard scale and exploring the causal relationships using a mixed methods research design comprising including in-depth interviews and survey research. The resultant performance management scale is measured by six perspectives including society and environment and an additional perspective of ‘health and safety’ is proposed in the post-hoc analysis to account for global pandemics, particularly the topical COVID-19 pandemic situation. The model illustrates the presence of complex relationships between the six perspectives. Further, the developed scorecard can allow hotel managers to be more cognizant by enabling them to uncover which facets of their service (customer, employee, or processes) are impacting the hotel's financial and sustainability performance and take appropriate strategic decisions.  Other Information Published in: Tourism Management Perspectives License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.tmp.2023.101141